Epidemiological Imaginaries of the Social: Epidemiologists and Pathologies of Modernization in Postcolonial Africa. (18th August 2020) - Reubi, David
Abstract: There is a growing anthropological literature analyzing the place that epidemiological surveillance occupies in contemporary global health. In this article, I build on this literature and take it into new directions by exploring what I call the epidemiological imaginaries of the social. Drawing on science and technology studies, I suggest that epidemiologists help make up the world, articulating complex and normatively loaded visions of social life that both enable and constrain action. More specifically, I argue that epidemiologists tell stories about the type of societies and people that compose the world and that these stories often shape global health policies and programs in powerful ways. To substantiate this argument, I examine epidemiologists' efforts to map smoking in postcolonial Africa, documenting how they have imagined smokers and smoking through the lense of modernization theory and showing how these imaginaries have shaped tobacco control policies in the region up to this day.